Numerical modelling of the interaction between flexible net panels and fluids using SPH method - Shi, Qian; Zhao, Depeng; Xue, Dawen; Zhang, Ning; Zhang, Lifeng; Pan, Yun (Frontiers in Marine Science, 2024)
This study addresses the challenge of simulating fluid flow around flexible net panels, which are critical components in aquaculture systems. Traditional grid-based Eulerian methods struggle with the complex deformations and interactions of such panels. To fill this gap, a numerical approach leveraging the Smoothed Particle Hydrodynamics (SPH) method is introduced. The proposed approach employs a knot-spring model to represent the flexible net panels. The nets are idealized as a structure of physical net-knots linked by virtual elastic springs. The SPH method is used to simulate the fluid flow, capturing the movement of the knots and the resulting deformation of the nets. The model's parameters and numerical schemes are detailed, along with the implementation process. The accuracy of the model is validated through comparisons with existing experimental and simulation data. The results indicate that the SPH-based approach accurately simulates the flow past flexible net panels, providing a detailed velocity distribution and deformation analysis. The study's findings demonstrate the potential of the SPH method for aquaculture engineering applications. The proposed approach offers a promising alternative to traditional methods, particularly in scenarios involving significant net deformation or interaction with other objects. The implications for the design and operation of aquaculture facilities are discussed, along with suggestions for future research directions.